Reviews of recent publications (Studies in 20th & 21st Century Literature, 2010)
Anne Fuchs, Mary Cosgrove, and Georg Grote. German Memory Contests: The Quest for Identity in Literature, Film, and Discourse since 1990 by Helen Cafferty Herschel Farbman. The Other Night: Dreaming, Writing, and Restlessness in Twentieth-Century Literature by Sidney Feshbach Richard Neupert. A History of the French New Wave Cinema by Candice Nicolas Dianne Marie Zandstra. Embodying Resistance: Griselda Gambaro and the Grotesque by James Gustafson Matthew J. Marr. Postmodern Metapoetry and the Replenishment of the Spanish Lyrical Genre, 1980-2000 by John Wilcox Gail A. Bulman. Staging Words, Performing Worlds: Intertextuality and Nation in Contemporary Latin American Theater by Patricia Tomé Alex E. Blazer. I Am Otherwise: The Romance Between Poetry and Theory after the Death of the Subject by Salah Khan Marcelline Block. Situating the Feminist Gaze and Spectatorship in Postwar Cinema by Marzia Caporale
Keywords: Anne Fuchs; Mary Cosgrove; Georg Grote; German Memory Contests: The Quest for Identity in Literature Film and Discourse since 1990; Helen Cafferty; Herschel Farbman; The Other Night: Dreaming Writing and Restlessness in Twentieth-Century Literature; Sidney Feshbach; Richard Neupert; A History of the French New Wave Cinema; Candice Nicolas; Dianne Marie Zandstra; Embodying Resistance: Griselda Gambaro and the Grotesque; James Gustafson; Matthew J. Marr; Postmodern Metapoetry and the Replenishment of the Spanish Lyrical Genre 1980-2000; John Wilcox; Gail A. Bulman; Staging Words Performing Worlds: Intertextuality and Nation in Contemporary Latin American Theater; Patricia Tomé; Alex E. Blazer; I Am Otherwise: The Romance Between Poetry and Theory after the Death of the Subject; Salah Khan; Marcelline Block; Situating the Feminist Gaze and Spectatorship in Postwar Cinema; Marzia Caporale